Trapping of free-living, unfed adult and nymphal Amblyomma hebraeum in heartwater endemic areas of South Africa, and the prevalence of Cowdria ruminantium in a sample of adult ticks - Venter, Estelle Hildegard (University of Pretoria, 2013)
Dissertation (MMedVet)--University of Pretoria, 2000.